Dry-method electrode, preparation method thereof and secondary battery
By premixing the active main material and conductive agent, frozen crushing binder in the preparation of dry electrodes and mixing at low temperature, combining kneading and rolling processing, and finally combining with the current collector hot rolling, the problems of uneven dispersion of dry electrode powder and mechanical opposite-likeness of the pole sheet are solved, and the first effect and cycling performance of the battery are significantly improved.
Patent Information
- Application Number
- CN202311264661.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-27
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2043-09-27
AI Technical Summary
During the preparation process of dry electrodes, there are problems such as uneven dispersion of powder, large abnormality in the mechanical properties of the polar sheet, low first efficiency of the whole battery, and poor circulation.
A dry electrode preparation method is adopted, including premixing active main material and conductive agent, frozen crushing binder, low-temperature mixing, kneading treatment, rolling film formation and hot rolling composite with current collector.
It significantly improves the uniformity of powder dispersion and dry film strength, reduces the various anisotropy of the electrode sheet, and improves the first effect and cycle life of the entire battery.
Smart Images

Figure CN119725392A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a dry electrode and a preparation method thereof, and a secondary battery. Background Art
[0002] With the rapid development of new energy technologies, the power and energy storage industries dominated by lithium-ion batteries have continuously put forward new requirements for the energy density and cost of batteries. In order to improve the energy density of batteries, the main development directions of batteries at present include: development of high-gram capacity main materials, development of high-performance auxiliary materials, development of thick electrodes, etc. Among them, thick electrodes are the simplest and most effective way to improve battery energy density. However, when using conventional wet slurry and coating processes to prepare thick electrodes, problems such as low coating thickness, poor peeling force, cracking of pole pieces, and high resistance are prone to occur.
[0003] Compared with conventional wet electrodes, dry electrodes have the following advantages: no solvents, no drying ovens and solvent recovery units are required, and equipment investment and energy consumption are significantly reduced; there is no binder floating problem, and thick electrodes can be prepared; the binder in the dry electrode is distributed in fibers, and the electrical contact between the conductive agent and the active main material is more complete, which can improve the electrode compaction density and rate performance. However, dry electrodes also have problems such as uneven powder dispersion, low strength of fiberized self-supporting films, weak adhesion between the dry film layer and the current collector, and poor first efficiency of the full battery.
[0004] Therefore, it is necessary to provide a dry electrode and a preparation method thereof and a secondary battery to solve the above problems. Summary of the invention
[0005] In view of the above shortcomings of the prior art, the present invention provides a dry electrode and a preparation method thereof and a secondary battery to improve the problems of uneven dispersion of dry electrode powder, low tensile strength of dry membrane and poor initial efficiency of the whole battery.
[0006] To achieve the above-mentioned purpose and other related purposes, the present invention provides a method for preparing a dry electrode, which method includes: a premixing step, premixing an active main material and a conductive agent to obtain a first mixture; a pretreatment step, freeze-crushing the binder to obtain a binder powder; a mixing step, mixing the first mixture and the binder powder to obtain a second mixture; a kneading step, kneading the second mixture to obtain a pole piece powder; a rolling step, rolling the pole piece powder into a film to obtain a dry membrane; and a compounding step, hot rolling the dry membrane and the collector to obtain a dry electrode.
[0007] In one example of the present invention, the premixing step includes: mixing the active main material and the conductive agent at a linear speed of 100 to 200 m / s for 1 to 2 hours.
[0008] In one example of the present invention, in the pretreatment step, the working temperature of the freeze-crushing treatment is -100 to -20°C, and the particle size of the binder powder obtained after the freeze-crushing treatment is 20 to 100 μm.
[0009] In one example of the present invention, the mixing temperature of the mixing step is -50 to 10°C; and / or, the mixing step further includes a process of heat treating the second mixture, and the heat treatment temperature is 80 to 200°C.
[0010] In one example of the present invention, the kneading temperature of the kneading step is 100-200°C; and / or, the kneading step also includes a conveying process of the kneaded electrode powder, and during the conveying process, the kneaded electrode powder is insulated at a temperature of 80-150°C.
[0011] In one example of the present invention, the rolling step uses a hot rolling process to roll the pole piece powder into a film, wherein the hot rolling temperature is 100-300° C., the roller diameter is 160-360 mm, and the rolling speed is 10-50 m / min.
[0012] In one example of the present invention, after the rolling step, the dry membrane is further subjected to surface lithium replenishment, and the surface lithium replenishment includes sieving the lithium replenisher powder and attaching it to the surface of the dry membrane, and hot pressing and compacting it on the surface of the dry membrane; wherein the hot pressing and compacting temperature is 80 to 150°C, and the porosity of the dry membrane after compaction is 30% to 45%.
[0013] In an example of the present invention, in the compounding step, the temperature of the hot rolling compounding is 100-200° C., and the porosity of the dry-process electrode obtained after compounding is 25%-35%.
[0014] Another aspect of the present invention provides a dry electrode, which is prepared by the preparation method described above.
[0015] The present invention further provides a secondary battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the positive electrode sheet and / or the negative electrode sheet are prepared by the preparation method of the present invention.
[0016] The preparation method of the dry electrode of the present invention first premixes the active main material and the conductive agent, freezes and crushes the binder into a binder powder with a small particle size, and then mixes the pretreated binder powder with the active main material and the conductive agent at low temperature, and then sequentially kneads, rolls to form a film, and hot rolls with the current collector to prepare the dry electrode. Premixing the active main material and the conductive agent can reduce the agglomeration of the conductive agent and the active main material, and at the same time achieve uniform coating of the conductive agent on the surface of the main material, thereby enhancing the electrical contact of the main material; freezing and crushing the binder into a powder with a small particle size can increase the specific surface area of the binder, so that it can fully contact with the active main material and the conductive agent, improve the dispersion uniformity, and make the dry electrode film have high strength and small anisotropy, which is beneficial to improving the rate and cycle performance of the battery.
[0017] In addition, mixing the active main material, conductive agent and binder at low temperature can effectively inhibit the premature fiberization of the binder. The fine binder is in full contact with the active main material and conductive agent at low temperature and high speed, and the mixing is more uniform. During the kneading process, the binder is fiberized under high shear force, forming a rich fiber network between the main material and the conductive agent, which significantly improves the adhesion strength of the dry membrane. At the same time, the small particle size of the binder can effectively reduce the mechanical anisotropy of the dry membrane, and the film forming processability is significantly improved. The fiberized powder is transported at high temperature to effectively improve the flexibility and looseness of the powder and improve the dry film forming performance. The dry membrane is surface-replenished with lithium before thermal compounding with the current collector. The lithium replenisher adheres to the surface of the electrode, which can effectively improve the first effect of the dry electrode. At the same time, the gas produced by the lithium replenisher placed on the surface has been discharged, which significantly improves the cycle performance of the entire battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0019] Figure 1 is a flowchart of a method for preparing a dry electrode according to an embodiment of the present invention;
[0020] Figure 2 is a flow chart of a method for preparing a dry electrode according to another embodiment of the present invention;
[0021] Figure 3 A schematic diagram of the structure of a dry electrode according to an embodiment of the present invention;
[0022] Figure 4 Schematic diagram of the sample for dry electrode tensile test of the present invention.
[0023] Reference numerals
[0024] 1. Current collector; 11. Metal foil; 12. Carbon layer; 2. Dry membrane layer; 3. Lithium replenishing layer. DETAILED DESCRIPTION
[0025] The following is an explanation of the embodiments of the present invention by specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the features in the following embodiments and the embodiments can be combined with each other without conflict. It should also be understood that the terms used in the embodiments of the present invention are intended to describe specific embodiments, rather than to limit the scope of protection of the present invention. The test methods for which specific conditions are not specified in the following examples are usually carried out under conventional conditions or according to the conditions recommended by the manufacturers.
[0026] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0027] Unless otherwise specified or incompatible herewith, the terms and phrases used herein shall have the following meanings:
[0028] As used herein, "plurality", "multiple", "multiple times", etc., unless otherwise specified, refer to a quantity greater than or equal to 2. For example, "one or more" means one or greater than or equal to two.
[0029] Herein, "preferred", "better" and "more preferred" are only used to describe implementation methods or examples with better effects, and it should be understood that they do not constitute a limitation on the scope of protection of the present invention. If multiple "preferred" items appear in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "preferred" item is independent.
[0030] Herein, “further”, “furthermore”, “particularly”, etc. are used for descriptive purposes to indicate differences in content, but should not be construed as limiting the scope of protection of the present invention.
[0031] In this article, when it comes to numerical ranges, unless otherwise specified, the distribution of optional values within the numerical range is considered continuous and includes the two numerical endpoints (i.e., the minimum value and the maximum value) of the numerical range, as well as every value between the two numerical endpoints. When multiple numerical ranges are provided to describe features or characteristics, these numerical ranges can be combined.
[0032] At present, dry-process electrodes have problems such as uneven powder dispersion, low strength of fibrous self-supporting films, weak adhesion between dry-process film layers and current collectors, and poor first efficiency of the entire battery. Patent CN114759158A provides a method for improving the adhesion of dry-process electrodes, which uses a porous current collector and a dry-process membrane for compounding. The rough surface of the porous current collector enhances the interface contact, thereby improving the strength of the dry-process electrode. However, the porous current collector has low tensile strength and is prone to band breakage during thermal compounding. Patent CN114335409A uses carbon-coated foil as the current collector, and improves the adhesion of the coating by adding hot melt adhesive to the carbon-coated layer. However, the hot melt adhesive is difficult to disperse and evenly coat on the surface of the current collector, and also increases the interface resistance of the coating.
[0033] Therefore, the present invention provides a method for preparing a dry electrode, a dry electrode prepared by the method, and a secondary battery comprising the dry electrode, which can improve the problems of uneven powder dispersion, large mechanical anisotropy of the electrode, low initial efficiency of the whole battery, and poor cyclability during the preparation process of the dry electrode.
[0034] See also Figure 1 The method for preparing the dry electrode of the present invention comprises at least the following steps:
[0035] S1, a premixing step, premixing the active main material and the conductive agent to obtain a first mixed material;
[0036] S2, a pretreatment step, freezing and crushing the binder to obtain a binder powder;
[0037] S3, a mixing step of mixing the first mixed material and the binder powder to obtain a second mixed material;
[0038] S4, a kneading step, kneading the second mixed material to obtain a pole piece powder;
[0039] S5, a rolling step, rolling the electrode powder into a film to obtain a dry-process membrane;
[0040] S6, a compounding step, compounding the dry process membrane sheet and the current collector by hot rolling to obtain a dry process electrode sheet.
[0041] The active main material in step S1 is the main active substance participating in the electrochemical reaction in the dry electrode, and the selection of the active main material is related to the type of dry electrode and battery. For example, taking a lithium-ion battery as an example, when the dry electrode is a dry positive electrode, the active main material can be selected from one or more of lithium-rich positive electrode materials such as lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, lithium iron manganese phosphate, and lithium nickel cobalt manganese oxide, that is, the active main material can be selected from any one of the above-listed materials, for example, lithium iron phosphate, or lithium nickel cobalt manganese oxide, etc.; any two or more combinations of the above-listed materials can also be selected, for example, a combination of lithium manganese oxide and lithium cobalt oxide, or a combination of lithium iron phosphate and lithium nickel cobalt manganese oxide, or a combination of lithium iron phosphate, lithium iron manganese phosphate and lithium nickel cobalt manganese oxide, etc. When the dry electrode is a dry negative electrode, the active main material is selected from one or more of graphite, silicon-carbon negative electrode, lithium titanate, soft carbon, and hard carbon, and the graphite is selected from artificial graphite and / or natural graphite. That is, the active main material can be selected from any one of the materials listed above, for example, artificial graphite; or hard carbon; or soft carbon, etc.; the active main material can also be selected from any combination of two or more of the materials listed above, for example, a combination of artificial graphite and hard carbon; or a combination of soft carbon and hard carbon; or a combination of artificial graphite, hard carbon and soft carbon, etc., which are not listed here one by one. When the active main material is a combination of two or more materials, there is no restriction on the ratio between the components in the combination, and they can be mixed in any ratio.
[0042] The role of the conductive agent in step S1 is to improve the electronic conductivity. In order to ensure that the battery has good charge and discharge performance, it plays the role of collecting microcurrents between the active main materials and between the active main materials and the current collector to reduce the contact resistance of the battery and accelerate the movement rate of electrons. The conductive agent can also improve the processability of the electrode, promote the infiltration of the electrolyte into the electrode, and effectively improve the migration rate of lithium ions in the battery material, thereby improving the charge and discharge efficiency of the battery and the service life of the lithium battery. The conductive agent includes but is not limited to one or more of carbon black, acetylene black, carbon nanotubes, carbon fiber, graphene, gold powder, and silver powder, that is, the conductive agent can be any one of the materials listed above, or it can be a combination of any two or more of the materials listed above. For example, the conductive agent is carbon black; or carbon nanotubes; or a combination of carbon black and acetylene black; or a combination of carbon fiber, acetylene black and graphene. It should be noted that when the conductive agent is a plurality of compositions, there is no restriction on the ratio between the components in the composition, and it can be mixed in any proportion.
[0043] Step S1 premixes the active main material and the conductive agent, which can fully disperse the conductive agent and the active main material, reduce the agglomeration of the conductive agent and the active main material, and at the same time, high-speed dispersion can achieve uniform coating of the conductive agent on the surface of the active main material, enhance the electrical contact of the active main material, and improve its conductivity. In some embodiments, the specific steps of premixing the active main material and the conductive agent are: placing the active main material and the conductive agent in a premixing device, such as a high-speed disperser, and mixing them for 1 to 2 hours at a line speed of 100 to 200 m / s to fully mix the active main material and the conductive agent. As an example, the line speed can be 100 m / s, 150 m / s or 200 m / s, etc. When premixing, the line speed is too low to meet the uniform dispersion of the active main material and the conductive agent, and the line speed is too high to easily cause the structural destruction of the active main material particles. Therefore, setting the premixing line speed at 100 to 200 m / s and the premixing time at 1 to 2 hours can not only meet the full mixing of the active main material and the conductive agent, but also will not destroy the material structure of the active main material.
[0044] See also Figure 1 , the main function of the binder in step S2 is to bond the active main material and the conductive agent. In the dry electrode, the binder is selected from a binder that can be fibrous, such as polytetrafluoroethylene (PTFE), carboxymethyl cellulose (CMC), polyvinylidene fluoride (PVDF) One or more, preferably PTFE, PTFE molecules F atoms are symmetrical, CF two elements are covalently combined, there are no free electrons in the molecule, the whole molecule is neutral, so that PTFE has excellent dielectric properties. Because there is an inert fluorine-containing shell outside the PTFE molecule, it has outstanding non-stick properties and low friction coefficient. In addition, the hexagonal crystal PTFE molecule has low cohesion between adjacent chains, and it is easier to slide along the chain axis (c-axis of the hexagonal system). When a shear load is applied to the PTFE crystal, crystal slip occurs along the c-axis, and the shape of the PTFE crystal changes, forming a nanofiber structure with a high aspect ratio.
[0045] Since the PTFE binder powder has a large particle size, it is easy to be fibrosed in advance when dispersed at a temperature higher than room temperature, resulting in the binder and the active main material and the conductive agent not being evenly dispersed, affecting the battery performance. Step S2 uses the freezing crushing technology to first harden and brittle the PTFE material at an extremely low temperature, and then crush it into small particles of PTFE under shearing. The fine PTFE binder has a large specific surface area and is easy to fully contact with the active main material and the conductive agent, thereby improving the uniformity of dispersion. The obtained dry electrode film has high strength and small anisotropy, which is beneficial to improving the rate performance and cycle performance of the battery.
[0046] In some embodiments, the specific process of the freeze-crushing treatment in step S2 is as follows: add the binder to the freeze-crushing machine, set the working temperature to -100℃~-20℃, and the freeze-crushing time to 30~60min; obtain the binder powder with a particle size of 20~100μm after the freeze-crushing treatment. Among them, the working temperature during the freeze-crushing treatment can be -100℃, -80℃, -50℃ or -20℃, etc., and the treatment time is 30min, 40min, 50min or 60min; the particle size of the binder powder obtained after the freeze-crushing treatment can be 20μm, 50μm, 70μm or 100μm, etc. When the freeze-crushing temperature is too high and exceeds the embrittlement temperature of the binder, it is difficult to crush the particles. When the freeze-crushing temperature is too low, the mechanical unit of the equipment will be damaged and metal chips will be introduced.
[0047] It should be noted that the ratio of active main material, conductive agent and binder can be set according to conventional ratios and is not limited here. Step S1 and step S2 can be performed in no particular order and can be performed simultaneously, or step S1 can be performed first and then step S2; or the order of step S1 and step S2 can be interchanged.
[0048] See also Figure 1 , step S3 is to mix the first mixture obtained in step S1 and the binder powder obtained in step S2 at low temperature to obtain a second mixture. Mixing under low temperature conditions can effectively inhibit the premature fiberization of the binder, and at low temperature and high speed, the fine binder powder can fully contact with the active main material and the conductive agent, and the mixing is more uniform. As an example, the temperature of low-temperature mixing is -50°C to 10°C, for example, -50°C, -30°C, -10°C or 10°C, etc.; the time of low-temperature mixing is 30min to 60min, for example, 30min, 50min or 60min, etc.
[0049] See also Figure 2 Preferably, in some embodiments, after step S3, the second mixed material is further subjected to a heat treatment process, that is, the second mixed material after low temperature mixing is subjected to a heat treatment at 80-200°C. The heat treatment process helps soften and loosen the binder, which is beneficial to the subsequent fiberization process (kneading process). In some embodiments, the heat treatment temperature can be 80°C, 120°C, 160°C or 200°C, etc., and the heat treatment time can be 1-2h, for example, 1h, 1.5h or 2h, etc.
[0050] See also Figure 1In step S4, the second mixture obtained in step S3 is kneaded to make it fiberized under high shear force. The binder in the second mixture forms a rich fiber network between the active main material and the conductive agent, which significantly improves the adhesion strength of the dry film. At the same time, since the binder is frozen and crushed, the binder with a small particle size can effectively reduce the mechanical anisotropy of the dry film, so that the film forming processability is significantly improved. In the present application, the kneading temperature is 100°C to 200°C, for example, 100°C, 140°C, 170°C or 200°C.
[0051] See also Figure 2 Preferably, in some embodiments, after the kneading step is completed, the pole piece powder is also transported, that is, the pole piece powder obtained after kneading is transported to the next process. During the transportation process, the pole piece powder needs to be heat-insulated, which can effectively improve the flexibility and looseness of the powder and improve the dry film forming performance; wherein, the temperature of the heat-insulating treatment is 80-150°C, for example, 80°C, 100°C or 150°C, and so on.
[0052] See also Figure 1 , step S5 rolls the electrode powder obtained in step S4 into a film to obtain a dry film. Specifically, the film forming is carried out by a hot rolling process, that is, the electrode powder is pressed into a continuous self-supporting film by a three-roller press, and then a multi-roller press arranged in a row performs multi-stage thinning to obtain a dry film of the required thickness. Among them, the parameters of the hot rolling process are: the rolling temperature is 100-300°C, the roller diameter Φ of the hot rolling equipment is 160-360mm, and the rolling speed is 10-50m / min. In some embodiments, the rolling temperature can be 100°C, 200°C or 300°C, etc.; the roller diameter can be 160mm, 230mm, 300mm or 360mm, etc.; the rolling speed can be 10m / min, 30m / min, 50m / min, and so on.
[0053] See also Figure 1 , step S6 composites the dry film obtained in step S5 with the current collector to form a dry electrode. Among them, the current collector is a carbon-coated metal foil, such as carbon-coated copper foil, carbon-coated aluminum foil, etc. For the dry positive electrode, the current collector is a carbon-coated aluminum foil; for the dry negative electrode, the current collector is a carbon-coated copper foil. Specifically, the dry film and the current collector are composited by hot rolling, and the temperature of the hot rolling composite is 100-200°C, for example, 100°C, 150°C or 200°C, and so on. After hot rolling, the porosity of the obtained dry electrode is 25% to 35%, for example, 25%, 30% or 35%, and so on.
[0054] See also Figure 2Preferably, in some embodiments, before the dry process membrane and the current collector are composited, the dry process membrane is also supplemented with lithium on the surface, which can effectively improve the initial effect of the dry process electrode. At the same time, the gas generation of the lithium supplement placed on the surface has been eliminated, which can significantly improve the cycle performance of the full battery. The specific process of surface lithium supplement is as follows: the lithium supplement powder is sieved and attached to the surface of the dry process membrane, and hot pressed and compacted on the surface of the dry process membrane. Among them, the lithium supplement is selected according to the type of dry process electrode. Some electrodes are dry positive electrodes, and the lithium supplement includes but is not limited to Li5FeO4 and / or Li2NiO2; some electrodes are dry negative electrodes, and the lithium supplement includes but is not limited to stabilized metal lithium powder (SLMP). The temperature of hot pressing and compacting is 80-150°C, for example, 80°C, 120°C or 150°C, etc.; the porosity of the compacted dry process membrane is 30%-45%, for example, 30%, 40% or 45%, etc. The amount of lithium supplement added is set according to the type of lithium supplement and the performance of the active main material.
[0055] The preparation method of the dry electrode of the present invention can significantly improve the powder dispersion uniformity and dry film strength, reduce the anisotropy of the pole piece, and improve the first efficiency and cycle life of the whole battery.
[0056] See also Figure 3 The dry electrode of the present invention is prepared by the above-mentioned preparation method, which can be a dry positive electrode or a dry negative electrode. The dry electrode can be used in secondary batteries such as lithium ion batteries and sodium ion batteries.
[0057] See also Figure 3 In one embodiment, the dry electrode includes a current collector 1 and a dry membrane layer 2, wherein the current collector 1 is a carbon-coated metal foil, which includes a metal foil 11 and a carbon layer 12 coated on the metal foil 11; the current collector 1 has two opposite surfaces along the thickness direction, and the dry membrane layer 2 is arranged on at least one surface of the current collector 1. Preferably, the dry membrane layer 2 is arranged on both surfaces of the current collector 1.
[0058] See also Figure 3 Preferably, the dry electrode also includes a lithium replenishing layer 3, and the lithium replenishing layer 3 is arranged on the dry membrane layer 2. The arrangement of the lithium replenishing layer 3 can effectively improve the initial effect of the dry electrode, and because the lithium replenishing layer 3 is formed by hot pressing the lithium replenishing agent on the surface of the dry membrane layer 2, the gas generated by the lithium replenishing agent has been eliminated, and the cycle performance of the whole battery can also be significantly improved.
[0059] The secondary battery of the present invention comprises a positive electrode sheet, a negative electrode sheet, a diaphragm and an electrolyte, wherein the diaphragm is arranged between the positive electrode sheet and the negative electrode sheet to play an isolation role; the electrolyte infiltrates the positive electrode sheet and the negative electrode sheet in the shell to play a role in conducting lithium ions; the positive electrode sheet and / or the negative electrode sheet are prepared by the preparation method described above in the present invention.
[0060] The technical scheme of the present invention is described in detail below through several specific examples and comparative examples. Unless otherwise specified, the raw materials and reagents used in the following examples are all commercially available products, or can be prepared by conventional methods in the art, and the instruments used in the examples are all commercially available.
[0061] Example 1
[0062] The dry electrode prepared in this embodiment is a dry positive electrode, and its active main material is NCM523 (LiNi 0.5 Co 0.2 Mn 0.3 ), the conductive agent is carbon black (SP) and carbon nanotubes (CNT), the binder is PTFE, and the mass percentage between the components is 95:2:1:2; the preparation method of the dry positive electrode is as follows:
[0063] (1) Premixing step: premix the active main material NCM523, the conductive agent SP and the CNT powder in a high-speed disperser of the premixing equipment. The dispersion line speed of the high-speed disperser is 150 m / s and the dispersion time is 1 h. After premixing, the surface of the NCM active main material is coated with SP and CNT to form a good electrical contact.
[0064] (2) Pretreatment step: adding the binder PTFE powder into a freezing mill for freezing and crushing, the freezing mill operating temperature is -80°C, the freezing and crushing time is 30 minutes, and the particle size of the crushed PTFE powder is D50 = 80 μm; the PTFE binder particle size is reduced, which is more conducive to uniform contact with the main material and the conductive agent;
[0065] (3) Mixing step: mixing the frozen and crushed PTFE powder with the pre-mixed active main material NCM523 and the conductive agent SP and CNT at low temperature, the low temperature mixing temperature is -10°C, and the low temperature mixing time is 30 minutes; the PTFE powder is not prone to premature fiberization under low temperature conditions, and high-speed stirring at low temperature can make the active main material, conductive agent, and binder fully dispersed and in contact;
[0066] (4) Heat treatment step: heat treatment the powder after low-temperature mixing at a temperature of 120° C. for 1 h. Heat treatment helps soften and loosen the PTFE binder, which is beneficial for subsequent fiberization treatment.
[0067] (5) Kneading step: placing the heat-treated powder in a kneader and subjecting the PTFE to high-speed shearing at high temperature to fiberize it, wherein the kneading temperature of the kneader is 150°C; high-temperature kneading can effectively improve the fiberization process of PTFE, so that a dense fiber network is formed between the NCM523 active main material and the conductive agent, which is conducive to dry film formation.
[0068] (6) Conveying step: conveying the kneaded powder to the lower hopper through a pipeline, and the conveying pipeline and the lower hopper are heat-insulated to maintain the powder temperature at 90° C.;
[0069] (7) Rolling step: The hot powder delivered to the lower hopper is pressed into a continuous self-supporting dry film by a three-roller press, and then multi-stage thinning is performed by a continuously arranged multi-roller press to obtain a NCM523 positive electrode dry film of the desired thickness; wherein, the rolling film formation and multi-stage thinning are performed by hot rolling, and the rolling temperature is 150°C.
[0070] (8) Surface lithium supplementation: The lithium supplement agent Li2NiO2 is evenly sprayed on the surface of the dry film through a high-speed vibrating screen, and then hot roller pressing is performed at a temperature of 100°C to compact and embed the sprayed lithium supplement agent particles on the surface of the dry film. The porosity of the dry film after compaction is 35%;
[0071] (9) Composite step: The dry film after surface lithium supplementation is double-sidedly thermally composited with the carbon-coated aluminum foil. The hot rolling temperature is 120° C. The porosity of the electrode after hot rolling is 30%, thereby obtaining the NCM523 dry-process positive electrode.
[0072] Example 2
[0073] The difference between this embodiment and embodiment 1 is that during the freeze crushing process in step (2), the operating temperature of the freeze crusher is -50°C and the freeze crushing time is 30 minutes.
[0074] Example 3
[0075] The difference between this embodiment and embodiment 1 is that during the mixing in step (3), the low-temperature mixing temperature is 10° C. and the low-temperature mixing time is 30 min.
[0076] Example 4
[0077] The difference between this embodiment and embodiment 1 is that the heat treatment temperature in step (4) is 150° C. and the heat treatment time is 1 hour.
[0078] Example 5
[0079] The difference between this embodiment and embodiment 1 is that the kneading temperature in step (5) is 180°C.
[0080] Example 6
[0081] The difference between this embodiment and embodiment 1 is that the rolling temperature of the hot rolling in step (7) is 180°C.
[0082] Example 7
[0083] The difference between this embodiment and embodiment 1 is that the lithium replenishing agent used in the surface lithium replenishment in step (8) is Li5FeO4.
[0084] Example 8
[0085] The difference between this embodiment and embodiment 1 is that the lithium replenisher used in step (8) for surface lithium replenishment is Li5FeO4, and the Li5FeO4 powder is evenly sprayed on the surface of the dry film by a high-speed vibrating screen, followed by hot rolling at a temperature of 120°C, to compact and embed the sprayed lithium replenisher particles on the surface of the dry film, and the porosity of the compacted dry film is 30%.
[0086] Example 9
[0087] The difference between this embodiment and embodiment 1 is that: in step (9), the dry film after surface lithium supplementation is double-sided thermally composited with the carbon-coated aluminum foil, the hot rolling temperature is 150° C., and the electrode porosity after hot rolling is 25%.
[0088] Example 10
[0089] The dry electrode prepared in this embodiment is a dry positive electrode, whose active main material is LiFePO4, the conductive agent is carbon black (SP) and carbon nanotubes (CNT), the binder is PTFE, and the mass percentage between the components is LiFePO4:SP:CNT:PTFE=94:2:1:3; the preparation method of the dry positive electrode is as follows:
[0090] (1) Premixing step: The active main material LiFePO4 and the conductive agent SP and CNT powder are premixed in a high-speed disperser of the premixing equipment. The dispersion line speed of the high-speed disperser is 200 m / s and the dispersion time is 1 h. After premixing, the surface of the LiFePO4 active main material is coated with SP and CNT to form a good electrical contact.
[0091] (2) Pretreatment step: adding the binder PTFE powder into a freezing mill for freezing and crushing, the freezing mill operating temperature is -100°C, the freezing and crushing time is 30 minutes, and the particle size of the crushed PTFE powder is D50 = 20 μm; the PTFE binder particle size is reduced, which is more conducive to uniform contact with the main material and the conductive agent;
[0092] (3) Mixing step: mixing the frozen and crushed PTFE powder with the premixed active main material LiFePO4 and the conductive agent SP and CNT at low temperature, the low temperature mixing temperature is -50°C, and the low temperature mixing time is 30 minutes; the PTFE powder is not prone to premature fiberization under low temperature conditions, and high-speed stirring at low temperature can make the active main material, conductive agent, and binder fully dispersed and in contact;
[0093] (4) Heat treatment step: heat treatment the powder after low-temperature mixing at a temperature of 200° C. for 1 h. Heat treatment helps soften and loosen the PTFE binder, which is beneficial for subsequent fiberization treatment.
[0094] (5) Kneading step: placing the heat-treated powder in a kneader and subjecting the PTFE to high-speed shearing at high temperature to fiberize it, wherein the kneading temperature of the kneader is 200°C; high-temperature kneading can effectively improve the fiberization process of PTFE, so that a dense fiber network is formed between the LiFePO4 active main material and the conductive agent, which is conducive to dry film formation.
[0095] (6) Conveying step: conveying the kneaded powder to the lower hopper through a pipeline, and the conveying pipeline and the lower hopper are subjected to heat preservation treatment to maintain the powder temperature at 100° C.;
[0096] (7) Rolling step: The hot powder delivered to the lower hopper is pressed into a continuous self-supporting dry film by a three-roller press, and then multi-stage thinning is performed by a continuously arranged multi-roller press to obtain a LiFePO4 positive electrode dry film of the desired thickness; wherein, the rolling film formation and multi-stage thinning are performed by hot rolling, and the rolling temperature is 300°C.
[0097] (8) Surface lithium supplementation: The lithium supplement agent Li2NiO2 is evenly sprayed on the surface of the dry film through a high-speed vibrating screen, and then hot roller pressing is performed at a temperature of 150°C to compact and embed the sprayed lithium supplement agent particles on the surface of the dry film. The porosity of the dry film after compaction is 45%;
[0098] (9) Composite step: The dry film after surface lithium supplementation is double-sided hot composited with carbon-coated aluminum foil, the hot rolling temperature is 100°C, and the porosity of the electrode after hot rolling is 35%, thereby preparing a LiFePO4 dry-process positive electrode.
[0099] Embodiment 11
[0100] The difference between this embodiment and embodiment 1 is that the active main material is LiFePO4, and the mass percentage of each component is: LiFePO4:SP:CNT:PTFE=94:2:1:3.
[0101] Example 12
[0102] The dry electrode prepared in this embodiment is a dry negative electrode, the active main material of which is artificial graphite, the conductive agent is carbon black (SP), the binder is PTFE, and the mass percentage between the components is artificial graphite: SP: PTFE = 96:2:2; the preparation method of the dry negative electrode is as follows:
[0103] (1) Premixing step: The active main material artificial graphite and the conductive agent SP powder are premixed in a high-speed disperser of the premixing equipment. The dispersion line speed of the high-speed disperser is 100 m / s and the dispersion time is 2 h. After premixing, the surface of the artificial graphite is coated with SP to form a good electrical contact.
[0104] (2) Pretreatment step: adding the binder PTFE powder into a freezing pulverizer for freezing and crushing, the freezing pulverizer operating temperature is -20°C, the freezing and crushing time is 30 minutes, and the particle size of the PTFE powder after crushing is D50 = 100 μm; the particle size of the PTFE binder is reduced, which is more conducive to uniform contact with the main material and the conductive agent;
[0105] (3) Mixing step: mixing the frozen and crushed PTFE powder with the premixed active main material artificial graphite and conductive agent SP at low temperature, the low temperature mixing temperature is -30°C, and the low temperature mixing time is 30 minutes; the PTFE powder is not prone to premature fiberization under low temperature conditions, and high-speed stirring at low temperature can make the active main material, conductive agent, and binder fully dispersed and in contact;
[0106] (4) Heat treatment step: heat treatment the powder after low-temperature mixing at 80° C. for 1 h. Heat treatment helps soften and loosen the PTFE binder, which is beneficial for subsequent fiberization treatment.
[0107] (5) Kneading step: placing the heat-treated powder in a kneader and subjecting the PTFE to high-speed shearing at high temperature to fiberize it, wherein the kneading temperature of the kneader is 100°C; high-temperature kneading can effectively improve the fiberization process of PTFE, so that a dense fiber network is formed between the artificial graphite and the conductive agent, which is conducive to dry film formation.
[0108] (6) Conveying step: conveying the kneaded powder to the lower hopper through a pipeline, and the conveying pipeline and the lower hopper are heat-insulated to maintain the powder temperature at 80° C.;
[0109] (7) Rolling step: The hot powder delivered to the lower hopper is pressed into a continuous self-supporting dry film by a three-roller press, and then multi-stage thinning is performed by a continuously arranged multi-roller press to obtain a negative electrode dry film of the desired thickness; wherein, the rolling film formation and multi-stage thinning are performed by hot rolling, and the rolling temperature is 100°C.
[0110] (8) Surface lithium replenishment: lithium metal powder is evenly sprayed on the surface of the dry film through a high-speed vibrating screen, followed by hot roller pressing at a temperature of 80°C to compact and embed the sprayed lithium replenisher particles on the surface of the dry film. The porosity of the compacted dry film is 30%;
[0111] (9) Composite step: The dry film after surface lithium supplementation is double-sidedly thermally composited with the carbon-coated aluminum foil. The hot rolling temperature is 200° C. The porosity of the electrode after hot rolling is 25%, thereby obtaining an artificial graphite dry-process negative electrode.
[0112] Embodiment 13
[0113] The dry electrode prepared in this embodiment is a dry negative electrode. The main material of the dry electrode is artificial graphite, the conductive agent is carbon black, the binder is PTFE, the mass percentage between the components is: artificial graphite: SP: PTFE = 96:2:2, the lithium supplement agent is metallic lithium powder, and the preparation process is the same as that of Example 1.
[0114] Comparative Example 1
[0115] The difference between this comparative example and Example 1 is that the dispersion linear velocity during premixing in step (1) is 50 m / s and the dispersion time is 1 h.
[0116] Comparative Example 2
[0117] The difference between this comparative example and Example 1 is that the dispersion linear velocity during premixing in step (1) is 250 m / s and the dispersion time is 1 h.
[0118] Comparative Example 3
[0119] The difference between this comparative example and Example 1 is that during the pretreatment in step (2), the operating temperature of the freezing crusher is -10°C, the freezing crushing time is 30 minutes, and the particle size of the PTFE powder after crushing is D50=250μm.
[0120] Comparative Example 4
[0121] The difference between this comparative example and Example 1 is that the mixing temperature during low-temperature mixing in step (3) is 20° C. and the mixing time is 30 min.
[0122] Comparative Example 5
[0123] The difference between this comparative example and Example 1 is that the conveying process in step (6) is carried out at room temperature.
[0124] Comparative Example 6
[0125] The difference between this comparative example and Example 1 is that: first, the NCM523 active main material and the conductive agent powder are premixed, and then PTFE powder is added for fiberization treatment; the fiberized powder is formed into a self-supporting film and thinned by the same method as in Example 1 to obtain an electrode dry film, and the prepared dry film is directly hot-rolled and composited with carbon-coated aluminum foil to obtain an NCM523 dry-process positive electrode.
[0126] Comparative Example 7
[0127] The active main material of the dry electrode in this comparative example is LiFePO4, and the mass percentage of each component is: LiFePO4:SP:CNT:PTFE=94:2:1:3. The preparation process is the same as that of comparative example 6.
[0128] Comparative Example 8
[0129] The main material of the dry electrode in this comparative example is artificial graphite, the conductive agent is carbon black, the binder is PTFE, and the mass percentage between the components is: artificial graphite: SP: PTFE = 96:2:2. The preparation process is the same as that of comparative example 6.
[0130] The dry electrodes prepared in Examples 1 to 13 and Comparative Examples 1 to 8 were subjected to performance tests. The test methods are shown below. The test results are shown in Table 1.
[0131] (1) Tensile strength test:
[0132] Cut 5 specimens along the longitudinal and transverse directions as required. The shape and size of the specimens are as follows. Figure 4 As shown. Measure the thickness of the sample in accordance with the national standard GB 6672. Measure the thickness of each sample at three points within the marking line and take the arithmetic mean. Mark the parallel part of the sample. When clamping the sample, the longitudinal axis of the sample should coincide with the center line of the upper and lower clamps of the testing machine, and the tightness should be appropriate. Start the testing machine at the specified speed ((250±50)mm / min) to perform the tensile test. After the sample breaks, read the load and the elongation of the marking line spacing to calculate the tensile strength.
[0133] (2) Electrode resistance test:
[0134] Use the electrode resistance tester to perform dry electrode resistance test. The dry electrode to be tested is placed between the two electrodes of the electrode resistance tester to start the test. The software automatically reads the electrode thickness, resistance, resistivity, conductivity and other data.
[0135] (3) Adhesion test:
[0136] Cut the thermally composited electrode into 20*100mm, use double-sided tape to stick the side to be tested on the stainless steel plate, and use a roller to compact it to make it fit the electrode completely. Fix one end of the stainless steel plate to the lower fixture of the tensile testing machine, fix the bent end of the sample to the upper fixture, and test the sample at a tensile speed of 50mm / min.
[0137] The dry electrodes prepared in Examples 1 to 13 and Comparative Examples 1 to 8 were assembled into cells, and the DCR (direct current resistance) performance and cycle performance tests were performed on the cells. The assembly process was as follows:
[0138] Examples 1 to 11 prepared dry-process positive electrodes, and Examples 12 and 13 prepared dry-process negative electrodes. When assembling the battery cells, the negative electrodes of Examples 1 to 11 were graphite negative electrodes prepared by the current conventional wet slurry process; the positive electrodes of Examples 12 and 13 were LFP positive electrodes prepared by the current conventional wet slurry process. The negative electrodes of the assembled battery cells of Comparative Examples 1 to 7 were graphite negative electrodes prepared by the current conventional wet slurry process, and the positive electrodes of the assembled battery cells of Comparative Example 8 were LFP positive electrodes prepared by the current conventional wet slurry process.
[0139] (4) DCR test
[0140] Charge the cell with 1 / 3C constant current to 4.2V, charge it with constant voltage to 0.05C, let it sit for 30min, discharge it with 1 / 3C0 to 3V, let it sit for 30min, and record the discharge capacity C0; charge it with 1 / 3C0 constant current to 4.2V, charge it with constant voltage to 0.05C0, let it sit for 30min, discharge it with 1 / 3C0 for 180min, let it sit for 10min, record the end voltage V0, discharge it with 2C for 30s, record the end voltage V1, and the discharge DCR = (V0-V1) / I.
[0141] (5) Cycle test:
[0142] Charge the cell with 1 / 3C constant current to 4.2V, charge it with constant voltage to 0.05C, let it sit for 30min, discharge it with 1 / 3C0 to 3V, let it sit for 30min, record the discharge capacity C0, charge it with 1 / 3C0 constant current to 4.2V, charge it with constant voltage to 0.05C0, let it sit for 30min, discharge it with 1 / 3C0 to 3V, let it sit for 30min, record the discharge capacity C1, and record the discharge capacity Cn at the end of each cycle in this way. The cycle capacity retention rate is Cn / C1*100%, and the record number of cycles N when the retention rate is 80%.
[0143] Table 1: Performance comparison of dry electrodes prepared in Examples 1 to 13 and Comparative Examples 1 to 8
[0144]
[0145] Comparing Examples 1 to 9 with Comparative Example 6, Examples 10 to 11 with Comparative Example 7, Examples 12 to 13 with Comparative Example 8, the results show that the tensile strength and bonding strength of the dry-process electrode prepared by the preparation method of the present invention are greater than those of the dry-process electrode prepared by the conventional method, and the electrode sheet resistance and the DCR value of the battery cell are both lower than those of the dry-process electrode prepared by the conventional method; the cycle performance of the battery cell is better than that of the battery cell prepared by the conventional method; this indicates that the preparation method of the present invention can significantly improve the powder dispersion uniformity and dry-process membrane strength, reduce the anisotropy of the electrode sheet, and improve the first efficiency and cycle life of the full battery.
[0146] By comparing Example 1 with Comparative Examples 1 and 2, it can be concluded that: in the pre-mixing step of the active main material and the conductive agent, if the dispersion line speed is too small, the active main material and the conductive agent cannot be fully dispersed, resulting in agglomeration and uneven dispersion, causing the electrode resistance and internal resistance to increase; if the dispersion line speed is too large, the active main material particles are prone to breakage, causing failure of the main material structure, and further affecting the cycle performance of the battery cell.
[0147] By comparing Example 1 and Comparative Example 3, it can be concluded that in the pretreatment step, the temperature of the freeze-crushing is too high, and the PTFE is difficult to be crushed into small particles, which affects its uniform dispersion and film-forming uniformity.
[0148] By comparing Example 1 and Comparative Example 4, it can be concluded that when mixing at low temperature, if the temperature is too high, the PTFE binder is prone to premature fiberization, and the conductive agent adheres to cause local agglomeration, affecting the uniformity of film formation.
[0149] By comparing Example 1 and Comparative Example 5, it can be concluded that if the powder is not subjected to heat preservation treatment during transportation, the fiberized powder will be cooled quickly and the film-forming stability will be poor.
[0150] In the preparation of the dry electrode, the active main material and the conductive agent are first pre-mixed at high speed, so that the conductive agent and the active main material can be fully dispersed, and the agglomeration of the conductive agent and the active main material can be reduced. At the same time, the high-speed dispersion can realize the uniform coating of the conductive agent on the surface of the active main material, and enhance the electrical contact of the active main material; the binder is frozen and crushed to obtain small particles of the binder. The fine binder has a large specific surface area and is easy to fully contact with the active main material and the conductive agent, thereby improving the dispersion uniformity. The obtained dry electrode film has high strength and small anisotropy, which is beneficial to improving the rate performance and cycle performance of the battery; mixing under low temperature conditions can effectively inhibit the premature fiberization of the binder, and the fine particles under low temperature and high speed can be crushed. Small binders are in full contact with the active main material and the conductive agent, and the mixture is more uniform; when kneaded at high temperature, the binder is fiberized under high shear force, forming a rich fiber network between the main material and the conductive agent, significantly improving the adhesion strength of the dry film, and at the same time, the fine binder can effectively reduce the mechanical anisotropy of the dry film, and the film forming processability is significantly improved; the fiberized powder is transported at high temperature, which can effectively improve the flexibility and looseness of the powder, and improve the dry film forming performance; before the dry film is thermally composited with the current collector, the surface lithium is supplemented, so that the lithium supplement agent is attached to the electrode surface, which can effectively improve the dry electrode first effect, and at the same time, the lithium supplement agent placed on the surface has produced gas and has been discharged, significantly improving the full battery cycle performance. Therefore, the present invention effectively overcomes some practical problems in the prior art and has a high utilization value and use significance.
[0151] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A method for preparing a dry electrode, characterized in that: include: A premixing step of premixing the active main material and the conductive agent to obtain a first mixed material; In a pretreatment step, the binder is subjected to a freeze-crushing treatment to obtain a binder powder; A mixing step of mixing the first mixed material and the binder powder to obtain a second mixed material; a kneading step, kneading the second mixed material to obtain a pole piece powder; A rolling step, rolling the electrode powder into a film to obtain a dry-process membrane; The compounding step is to compound the dry-process membrane with the current collector by hot rolling to obtain a dry-process electrode.
2. The preparation method according to claim 1, characterized in that: The premixing step includes: mixing the active main material and the conductive agent at a linear speed of 100 to 200 m / s for 1 to 2 hours.
3. The preparation method according to claim 1, characterized in that: In the pretreatment step, the working temperature of the freeze-crushing treatment is -100 to -20°C, and the particle size of the binder powder obtained after the freeze-crushing treatment is 20 to 100 μm.
4. The preparation method according to claim 1, characterized in that: The mixing temperature of the mixing step is -50 to 10°C; and / or, the mixing step further includes a process of heat treating the second mixed material, and the heat treatment temperature is 80 to 200°C.
5. The preparation method according to claim 1, characterized in that: The kneading temperature of the kneading step is 100-200°C; and / or, the kneading step also includes a conveying process for the kneaded electrode powder, and the kneaded electrode powder is kept warm during the conveying process, and the keeping temperature is 80-150°C.
6. The preparation method according to claim 1, characterized in that: The rolling step adopts a hot rolling process to roll the pole piece powder into a film, wherein the hot rolling temperature is 100-300° C., the roller diameter is 160-360 mm, and the rolling speed is 10-50 m / min.
7. The preparation method according to claim 1, characterized in that: After the rolling step, the dry-process membrane is further subjected to surface lithium replenishment, wherein the surface lithium replenishment comprises sieving lithium replenisher powder and attaching it to the surface of the dry-process membrane, and hot pressing and compacting the powder on the surface of the dry-process membrane; wherein the hot pressing and compacting temperature is 80 to 150° C., and the porosity of the dry-process membrane after compaction is 30% to 45%.
8. The preparation method according to any one of claims 1 to 7, characterized in that: In the compounding step, the temperature of the hot rolling compounding is 100-200° C., and the porosity of the dry-process electrode obtained after compounding is 25%-35%.
9. A dry electrode, characterized in that: The dry electrode is prepared by the preparation method described in any one of claims 1 to 8.
10. A secondary battery, characterized in that: It comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, and the positive electrode sheet and / or the negative electrode sheet are prepared by the preparation method according to any one of claims 1 to 8.
Citation Information
Patent Citations
Dry-method electrode, preparation method thereof, dry-method battery cell and battery
CN114335409A
Preparation method of dry-method electrode plate and secondary battery
CN114759158A
Preparation method of battery active layer, battery pole piece and application
CN113659104A
Method and system for preparing electrode plate by dry process, and application
CN113675362A
Dry method electrode production method and device
CN114914404A
Cited By
Mixing method of electrode material, preparation method of electrode diaphragm, battery pole piece, battery and electronic equipment
CN120545297A
Polymer binder for dry electrode films and method for manufacturing the same
KR102907398B1